Multi-hazard emergency management in historical centers: methods and tools for increasing mass-gathering safety in case of earthquake - Gabriele Bernardini; Chiara David; Silvia Santarelli; Enrico Quagliarini; Marco D'Orazio (Tema, 2018)
The use of historic city centers for touristic purposes, i.e. mass gatherings events (MEs), needs a multi-hazard approach which should jointly consider building heritage and hosted individuals’ emergency safety, by including effects of individuals’ behaviors to provide effective riskreduction strategies (i.e.: interventions on critical Building Heritage; outdoor spaces layout reorganization; emergency management; wayfinding systems;). This work evidences the capabilities of such approach in case of MEs-earthquake emergency combinations, by taking advantaging of a validated evacuation simulator, through a case-study application.